Over a million students use our free study notes to help them with their homework
When solving simultaneous equations, there are two methods: substitution and elimination. For this question, as one of the equations is a quadratic, the substitution method has to be used. The second equa...
common factor is 6x therefore it is 6x(x-2)
equation of tangent is y - y1 = m(x-x1). differentiating y gives us the value of m. so dy/dx = 4x-10. we know x is 3. therefore, dy/dx = m = 2 but we need equation of the normal, which is y-y1=(1/m)(x-x1)...
Student should use a combination of trigonometric identities, product rule and chain rule to find dy/dx.This can be done by applying product rule, obtainingdy/dx = sin(2x). d[cos(x)^2]/dx + cos(x)^2. d[si...
I would convert the sin squared theta into a cos squared theta using identity that sin sq + cos sq = 1This would then give me a quadratic equation which I would substitute X = cos thetaThen I would solve ...
←
614
615
616
617
618
→
Internet Safety
Payment Security
Cyber
Essentials